Biochar-based slow-release of fertilizers for sustainable agriculture: A mini review - Chongqing Wang; Dan Luo; Xue Zhang; Rong Huang; Yijun Cao; Gonggang Liu; Yingshuang Zhang; Hui Wang (Environmental Science and Ecotechnology, 2022)
Increasing global population and decreasing arable land pose tremendous pressures to agricultural production. The application of conventional chemical fertilizers improves agricultural production, but causes serious environmental problems and significant economic burdens. Biochar gains increasing interest as a soil amendment. Recently, more and more attentions have been paid to biochar-based slow-release of fertilizers (SRFs) due to the unique properties of biochar. This review summarizes recent advances in the development, synthesis, application, and tentative mechanism of biochar-based SRFs. The development mainly undergoes three stages: (i) soil amendment using biochar, (ii) interactions between nutrients and biochar, and (iii) biochar-based SRFs. Various methods are proposed to improve the fertilizer efficiency of biochar, majorly including in-situ pyrolysis, co-pyrolysis, impregnation, encapsulation, and granulation. Considering the distinct features of different methods, the integrated methods are promising for fabricating effective biochar-based SRFs. The in-depth understanding of the mechanism of nutrient loading and slow release is discussed based on current knowledge. Additionally, the perspectives and challenges of the potential application of biochar-based SRFs are described. Knowledge surveyed from this review indicates that applying biochar-based SRFs is a viable way of promoting sustainable agriculture.